1997
DOI: 10.1097/00004647-199702000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Characterization, and Functional Role of Phosphodiesterase Type IV in Cerebral Vessels: Effects of Selective Phosphodiesterase Inhibitors

Abstract: Summary:The role of the phosphodiesterase type IV iso zyme (PDE IV) in the regulation of cerebrovascular tone was investigated in the canine basilar artery in vitro and in vivo. The PDE isozymes extracted from the canine basilar artery were isolated by diethylaminoethanol (DEAE) Sepharose affinity chromatography and identified based on sensitivity to isozyme-selective PDE inhibitors. The family of phosphodiesterase (POE) isozymes is responsible for the intracellular hydrolysis of cAMP and cOMPo Some members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Several studies have also shown the dilatory effects of dipyridamole as more or less selective phosphodiesterase inhibitors on intact cerebral arteries (Harris et al, 1989;Cosentino et al, 1992;Parfenova et al, 1993;Rosenblum et al, 1993;Willette et al, 1997). The present study demonstrated that dipyridamole induced only small changes in [Ca 2+ ]i in testicular or cerebral arteriole smooth muscle cells, and no dilation was observed in these arterioles.…”
Section: Response Of Smooth Muscle Cells In Testicular and Cerebral Asupporting
confidence: 67%
“…Several studies have also shown the dilatory effects of dipyridamole as more or less selective phosphodiesterase inhibitors on intact cerebral arteries (Harris et al, 1989;Cosentino et al, 1992;Parfenova et al, 1993;Rosenblum et al, 1993;Willette et al, 1997). The present study demonstrated that dipyridamole induced only small changes in [Ca 2+ ]i in testicular or cerebral arteriole smooth muscle cells, and no dilation was observed in these arterioles.…”
Section: Response Of Smooth Muscle Cells In Testicular and Cerebral Asupporting
confidence: 67%
“…Denbufylline-induced relaxation in vitro was also significantly impaired in basilar arteries obtained from a model of chronic vasospasm. In conclusion, PDE4 appears to be the predominant isozyme regulating vascular tone via cAMP hydrolysis in cerebral vessels (Willette et al, 1997). Further investigation is needed to determine whether inhibition of PDEs activity might be a useful approach in patients with SAH.…”
Section: Subarachnoid Hemorrhagementioning
confidence: 95%
“…numerous mechanisms have been proposed (Delgado et a!., 1988;Edwards et a!., 1992;Svendgaard et a!., 1987;Well urn et a!., 1985;Willette et a!., 1997).…”
mentioning
confidence: 99%